ÓXIDOS DE MOLIBDÊNIO E COBRE, OBTIDOS PELO MÉTODO PECHINI E SEUS RESPECTIVOS ÓXIDOS MISTOS - Possebon, Roberta Cristina Veloso (2019)
Although there is a great diversity of materials used in transition-related metal oxides in the literature, often as synthesis routes large quantities of reagents, steps and low yields are used. Therefore, one of the major challenges of research is to develop low cost materials with unique features. Thus, this work will present a sample of molybdenum oxides (MoO3) and copper (CuO), and metal oxides of these metals using the Pechini Method, as their characterization and application in photocatalysis. As the advantages of this method stand out the versatility, the low cost, the simplicity and the short execution time for the analysis, besides the fact that until the present moment, there are few literature reports, where it is used the method for using these materials. Different materials were synthesized, including different mixed oxide filters, kept with matrix or molybdenum oxide. In addition, pure molybdenum and copper oxides were also synthesized for comparison purposes. All selected oxides were characterized by colorimetry, X-ray difrometry (XRD), scanning electron microscopy (SEM) and X-ray Dispersive Energy Spectroscopy (EDS), Infrared Spectroscopy (FTIR), Diffuse Reflectance Spectroscopy in the UV-Visible (DRS-UV-Vis), Electronic Spectroscopy (UV-Vis). With the characterizations performed, it was possible to determine the Pechini method for material display, and observe the XRD results, which have microparticulate size and high degree of crystallinity. UV-Vis spectroscopy demonstrates that pure molybdenum oxides and pure copper do not exhibit photocatalytic activity and degradation of reactive black dye 5, as well as measurement errors. Only one sample containing the highest concentration of copper metal shows significant activity.